COVID-19: Diagnostic methodologies (Research, Society and Development, 2021)
The first cases of COVID-19 were registered in the city of Wuhan (China) in December 2019. The disease caused by the new Coronavirus (SARS-CoV-2) initially affects the respiratory tract and its clinical effects can lead to organic dysfunction in the host. In this context, laboratory tests are diagnostic tools of great relevance for the detection of SARS-CoV-2, confirmation of the disease and evaluation of systemic dysfunctions caused by the virus. Thus, this study aimed to conduct an up-to-date about COVID-19 and discuss the diagnostic methodologies of SARS-CoV-2 and its effects in laboratory tests. The present study was performed between January 1st and May 31st, 2020 based on data from works published in scientific journals available in full. For that, PubMed, Science Direct and Scielo databases was used besides the following descriptors in English: coronavirus, covid-19, sars-cov-2, laboratory medicine, laboratory tests, laboratory findings, RT-PCR, immunochromatography and chemiluminescence. In total, 2810 related scientific articles were found, of which only 24 were considered relevant for the study. SARS-CoV-2 can be detected in respiratory samples using laboratory diagnostic methodologies such as RT-PCR (Real-time Polymerase Chain Reaction) or by detecting antibodies through immunochromatographic, immunosorbent and chemiluminescent tests. In addition, hematological changes related to the leukogram, changes in the coagulation panel, changes in liver and kidney markers as well as inflammatory markers can be observed. Finally, the diagnostic tools have been crucial for monitoring the patient with symptoms of COVID, providing support to clinicians in decision-making.